The use of Global Positioning Systems in elite rugby union - Cahill, N.; Worsfold, P.; Lamb, K. (World Congress of Performance Analysis of Sport IX, 2012)
Recent research has suggested that decrements in performance among team sports players towards the latter parts of matches are attributed to the onset of fatigue (Aughey, 2010; Austin & Kelly, 2012), which has the added cost of increasing their susceptibility to injury (Brookes et al., 2008). To date, however, little objective evidence exists on whether such decrements, particularly in terms of locomotive actions, occur in the sport of rugby union, which has one of the highest injury rates across all team sports (Brookes et al., 2005). Therefore the aim of this investigation was to identify whether notable changes occurred in important locomotive variables between the first and second halves and between the four quarters of matches played throughout the English Premiership. Following ethical approval, 98 elite rugby union players (age 27.0 ± 4.0 y; body mass 104.0 ± 13.0 kg; stature 1.87 ± 0.07 m) from 8 English Premiership Clubs were tracked using GPS SPI Pro 5 Hz units during 44 competitive Premiership matches played in the 2010/2011 season. Overall, 276 GPS data files compiled from these matches were analysed with GPSports Team AMS software. Locomotive performance was quantified for each player during the first and second halves of match play, and during each quarter via measures of metres covered per minute (m.min-1), maximum speed (km.h-1), and percentage of total distance covered whilst sprinting, striding, cruising, jogging and walking. The data were analysed by two positional groupings (Forwards/Backs and separately Front Row/Second Row/Back Row/Scrum Half/Inside Backs/Outside Backs) across the specified match periods using non-parametric statistics. The results highlighted significant (p < 0.05) reductions among all positional groups except Scrum Half in relative distance covered from the 1st to 4th quarter (as much as -13.5% for the Back Row and -12% for Front and Second Rows). Peak speed between the 1st and 4th quarter was also found to decrease among the Front Row (-11.6%) and Second Row (-10.2%) groups, but not among any other positional groups. These findings endorse those of Austin and Kelly (2012) who analysed 10-minute segments of a rugby league match, and, importantly, provide tangible support for the notion that movement-related fatigue is evident in the latter aspects of elite level rugby union matches. Such knowledge should be accommodated by coaches in their preparation and recovery schedules, and substitution policies.